The first widespread solar energetic particle event observed by Solar Orbiter on 2020 November 29 - Kollhoff A; Kouloumvakos A; Lario D; Dresing Nina; Gomez-Herrero R; Rodriguez-Garcia L; Malandraki OE; Richardson IG; Posner A; Klein KL; Pacheco D; Klassen A; et al. (EDP SCIENCES S A, 2022)
Context. On 2020 November 29, the first widespread solar energetic particle (SEP) event of solar cycle 25 was observed at four widely separated locations in the inner (less than or similar to 1AU) heliosphere. Relativistic electrons as well as protons with energies >50MeV were observed by Solar Orbiter (SolO), Parker Solar Probe, the Solar Terrestrial Relations Observatory (STEREO)-A and multiple near-Earth spacecraft. The SEP event was associated with an M4.4 class X-ray flare and accompanied by a coronal mass ejection and an extreme ultraviolet (EUV) wave as well as a type II radio burst and multiple type III radio bursts.
Aims. We present multi-spacecraft particle observations and place them in context with source observations from remote sensing instruments and discuss how such observations may further our understanding of particle acceleration and transport in this widespread event.
Methods. Velocity dispersion analysis (VDA) and time shift analysis (TSA) were used to infer the particle release times at the Sun. Solar wind plasma and magnetic field measurements were examined to identify structures that influence the properties of the energetic particles such as their intensity. Pitch angle distributions and first-order anisotropies were analyzed in order to characterize the particle propagation in the interplanetary medium.
Results. We find that during the 2020 November 29 SEP event, particles spread over more than 230 degrees in longitude close to 1AU. The particle onset delays observed at the different spacecraft are larger as the flare-footpoint angle increases and are consistent with those from previous STEREO observations. Comparing the timing when the EUV wave intersects the estimated magnetic footpoints of each spacecraft with particle release times from TSA and VDA, we conclude that a simple scenario where the particle release is only determined by the EUV wave propagation is unlikely for this event. Observations of anisotropic particle distributions at SolO, Wind, and STEREO-A do not rule out that particles are injected over a wide longitudinal range close to the Sun. However, the low values of the first-order anisotropy observed by near-Earth spacecraft suggest that di ffusive propagation processes are likely involved.